2020
DOI: 10.1093/chemse/bjaa052
|View full text |Cite
|
Sign up to set email alerts
|

Better Olfactory Performance and Larger Olfactory Bulbs in a Mouse Model of Congenital Blindness

Abstract: It is well established that early blindness results in enhancement of the remaining non-visual sensory modalities accompanied by functional and anatomical brain plasticity. While auditory and tactile functions have been largely investigated, the results regarding olfactory functions remained less explored and less consistent. In the present study, we investigated olfactory function in blind mice using three tests: the buried food test, the olfactory threshold test and the olfactory performance test. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 65 publications
4
15
0
Order By: Relevance
“…The question remains, how did they detect the wall or the border of the behavioral device, and which non-visual perceptions or sensory modalities contribute to spatial navigation in blind mice. A large body of evidence showed that early blindness (due to retinopathy of prematurity, glaucoma and cataract) results in an enhancement of the remaining non-visual modalities in humans (Van Boven et al, 2000;Beaulieu-Lefebvre et al, 2011;Renier et al, 2014), as well as in mice (Zhou et al, 2017;Touj et al, 2019Touj et al, , 2020Touj et al, , 2021a. All of these behavioral changes are supported by brain plasticity and reorganization (Kupers and Ptito, 2014;Chebat et al, 2020;Touj et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The question remains, how did they detect the wall or the border of the behavioral device, and which non-visual perceptions or sensory modalities contribute to spatial navigation in blind mice. A large body of evidence showed that early blindness (due to retinopathy of prematurity, glaucoma and cataract) results in an enhancement of the remaining non-visual modalities in humans (Van Boven et al, 2000;Beaulieu-Lefebvre et al, 2011;Renier et al, 2014), as well as in mice (Zhou et al, 2017;Touj et al, 2019Touj et al, , 2020Touj et al, , 2021a. All of these behavioral changes are supported by brain plasticity and reorganization (Kupers and Ptito, 2014;Chebat et al, 2020;Touj et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A large body of evidence showed that early blindness (due to retinopathy of prematurity, glaucoma and cataract) results in an enhancement of the remaining non-visual modalities in humans (Van Boven et al, 2000;Beaulieu-Lefebvre et al, 2011;Renier et al, 2014), as well as in mice (Zhou et al, 2017;Touj et al, 2019Touj et al, , 2020Touj et al, , 2021a. All of these behavioral changes are supported by brain plasticity and reorganization (Kupers and Ptito, 2014;Chebat et al, 2020;Touj et al, 2020). Compensatory mechanisms can be adopted to improve spatial and navigation skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In animals, it was shown that early visual deprivation induces an enhanced spatial hearing in ferrets (King & Parsons, 1999). In mice, early and late visual deprivation enhances olfactory performance (Touj et al., 2020) (Zhou et al., 2017). These behavioural changes are adaptive mechanisms that allow visually deprived individuals and animals to cope with their sensory loss.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer studies have successfully shown that late‐onset visual deprivation may induce tactile (Goldreich & Kanics, 2003; Legge et al., 2008) or auditory (Dufour et al., 2005) compensations in humans. In animals, both early and late visual deprivation for one week enhanced olfactory performance in rodents (Touj et al., 2020; Zhou et al., 2017).…”
Section: Introductionmentioning
confidence: 99%